2022
DOI: 10.1039/d1fo04334j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Passiflora setacea juice and its phenolic metabolites on insulin resistance markers in overweight individuals and on microglial cell activity

Abstract: Passiflora setacea (PS) is a species of wild Brazilian passion fruit, rich in bioactive compounds. Studies suggested that a diet rich in bioactive compounds can positively modulate inflammation and oxidative...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…One of these, 3,4-dihydroxyphenylacetic acid, was also tested for its capacity to stimulate insulin secretion in an in vitro model of pancreatic β-cells. In a similar fashion, the study conducted by Duarte et al [33] also shows that the intake of a Passiflora setacea juice containing mixed (poly)phenols had reducing effects on insulin and HOMA-IR. The authors extracted some of the plasma-sulfate-and glucuronide-derived metabolites, which were subsequently used to treat microglial cultured cells and showed some regulatory activity in biomarkers potentially related to anti-diabetic effects.…”
Section: Results From Verymentioning
confidence: 53%
“…One of these, 3,4-dihydroxyphenylacetic acid, was also tested for its capacity to stimulate insulin secretion in an in vitro model of pancreatic β-cells. In a similar fashion, the study conducted by Duarte et al [33] also shows that the intake of a Passiflora setacea juice containing mixed (poly)phenols had reducing effects on insulin and HOMA-IR. The authors extracted some of the plasma-sulfate-and glucuronide-derived metabolites, which were subsequently used to treat microglial cultured cells and showed some regulatory activity in biomarkers potentially related to anti-diabetic effects.…”
Section: Results From Verymentioning
confidence: 53%
“…Antioxidant activity, antimutagenic, antimicrobial [83,84,[84][85][86][87][88][89] Mauritiella armata Palmitic, estearic, oleic, linoleic, linolenic acid, tocopherol, and α-tocopherol Antioxidant activity [90] Myrcia bella Flavonoids and phenolic acids derivatives Antimutagenic and antioxidant activity [91] Passiflora setacea Polyphenols Antidiabetic and anti-inflammatory effect, with insulin, HOMA IR, PPAR-γ and IL-6 levels improvement [92] Pouteria ramiflora Friedelin, epifriedelanol, taraxerol, triterpens and FFA Antioxidant and α-amylase inhibition [93] Pouteria torta Phenolic compounds, flavonoids, catechin and epicatechin Antioxidant and α-amylase inhibition [94] Psidium cattleianum Epicatechin, gallic, coumaric, and ferulic acid, myricetin and quercetin Antioxidant and antimicrobial activity and antiproliferative effect on human cancer cells [95] Rollinia mucosa Phenolic compounds and tocopherols Antioxidant activity [56]…”
Section: Mauritia Flexuosamentioning
confidence: 99%
“…In individual male volunteers treated with P. setacea pulp, a significant reduction in insulin levels, HOMA IR, and IL-6 was observed. The plasma from the same individuals was used as a treatment in BV-2 microglial cells, and as a result, higher levels of PPAR-γ were observed in the cells, indicating an anti-inflammatory and antidiabetic effect [92].…”
Section: Adipocyte Differentiation Adipogenesis and Browningmentioning
confidence: 99%
“…According to Blüher (2020), even obese subjects considered metabolically healthy, with preserved insulin sensitivity, still present an important higher risk of type 2 diabetes than lean healthy subjects (BLÜHER, 2020). Despite other passion fruit species reporting effects of improving insulin sensitivity (DUARTE et al, 2022(DUARTE et al, , 2020, no alterations in glycemic profile were found for P.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies conducted in humans with P. setacea juice (250mL, only dose) administered to male overweight volunteers (n=12) resulted in decreased levels of insulin, insulin homeostatic model assessment for insulin resistance (HOMA-IR), and increased HDL compared to placebo (DUARTE et al, 2022(DUARTE et al, , 2020. Another study with P. setacea found that acute ingestion of the fruit by overweight men (n=15, single dose of 50g) decreased insulin, HOMA-IR, and increased IL-2 compared to placebo; while IL-6 and HOMA-IR increased in the placebo branch of the chronic ingestion study (n=9, 50g/day, 14 days) (DUARTE et al, 2022). The observed results suggest an anti-inflammatory and antidiabetic effect that could be attributed to the phenolic compounds in the fruit.…”
Section: The Passiflora Generamentioning
confidence: 99%